White roof as a multiple benefits low-cost technology: a state of the art - Francesco Giordano (CERN IdeaSquare Journal of Experimental Innovation, 2019)
The article explores the potentiality of white roof as an effective solution to address three interrelated problems which are global warming, urban heat island effect, energy consumption in buildings. First, the global warming and urban heat island effects are briefly explained. Later, the arisen of geoengineering approaches as potential solutions of such issues is explored. Among various solutions, the white roof technology is deeper analysed and its effects on building energy efficiency are investigated through literature results. Finally, the experiment done in the Idea Square of CERN is presented. Still, the application of white roofs in urban areas stands as compelling issue and how it can be improved is an open discussion.